2017
DOI: 10.1111/codi.13496
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance based texture parameters as potential imaging biomarkers for predicting long‐term survival in locally advanced rectal cancer treated by chemoradiotherapy

Abstract: Aim The study aimed to investigate whether textural features of rectal cancer on MRI can predict long-term survival in patients treated with long-course chemoradiotherapy.Method Textural analysis (TA) using a filtrationÀhis-togram technique of T2-weighted pre-and 6-week post-chemoradiotherapy MRI was undertaken using TexRAD, a proprietary software algorithm. Regions of interest enclosing the largest cross-sectional area of the tumour were manually delineated on the axial images and the filtration step extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Chee et al [21] found that homogeneous texture features (higher Uniformity, lower Entropy and lower SD) were connected with higher DFS in patients with locally advanced rectal cancer. Jalil et al [33] used texture analysis based on MRI to find that Kurtosis was the independent factor to predict DFS for CRC patients.…”
Section: Prognosis Analysismentioning
confidence: 99%
“…Chee et al [21] found that homogeneous texture features (higher Uniformity, lower Entropy and lower SD) were connected with higher DFS in patients with locally advanced rectal cancer. Jalil et al [33] used texture analysis based on MRI to find that Kurtosis was the independent factor to predict DFS for CRC patients.…”
Section: Prognosis Analysismentioning
confidence: 99%
“…Rectal MRI is essential for pre-and post-treatment assessment of rectal cancer, as it provides anatomic structures and their relationship with the tumor with a high-spatial resolution [22,23]. Rectal MRIbased radiomics have been used for treatment response [24], lymph-node metastasis [25], and prognostic evaluation [26]. However, MRI-based radiomics for LVI prediction remains underinvestigated in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Features obtained from TA have been used to help distinguish abnormal from normal tissues in the lung, liver, colon, breast, and prostate . MRI‐based TA of rectal cancers can assess the outcome and thus could potentially be used to select patients for individualized therapy . TA also can be used to evaluate the efficacy of radiotherapy.…”
mentioning
confidence: 99%
“…[16][17][18] MRI-based TA of rectal cancers can assess the outcome and thus could potentially be used to select patients for individualized therapy. 19 TA also can be used to evaluate the efficacy of radiotherapy. A few studies have focused on DCE-MRI scans to assess the pathological response after preoperative CRT for LARC, 19,20 although those studies mostly considered rectal cancer as a uniform mass or used a mean value to describe the whole tumor.…”
mentioning
confidence: 99%